STRATEGI GURU DALAM MENGIMPLEMENTASIKAN PENDEKATAN PEMBELAJARAN MENDALAM PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Qibtiah, Maria; Yantoro; Sholeh, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe teachers’ strategies in implementing deep learning approaches in mathematics learning at the elementary school level. Deep learning emphasizes conceptual understanding, critical thinking, and meaningful student engagement, which contrasts with traditional memorization-oriented learning. This research explores how teachers design learning experiences, select instructional methods, utilize media, and facilitate classroom interactions to build deeper mathematical comprehension. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation in an elementary school classroom. The results show that teachers implement several strategies such as contextual problem-based learning, the use of manipulatives, structured inquiry, reflective questioning, and collaborative discussions. These strategies encourage students to connect concepts, explore ideas actively, and construct meaning from learning experiences. The study concludes that implementing deep learning strategies supports students in developing stronger conceptual understanding and more independent thinking in mathematics learning.